The esc textbook of cardiovascular imaging - Zamorano, Jose Luis (Springer London, 2009)
The appropriate application of imaging procedures and accurate image interpretation are essential skills for the cardiologist. The ESC Council on Cardiovascular Imaging identified the need for a practical and yet comprehensive book covering all major imaging modalities. To achieve this goal, the distinguished Editors have assembled a team of imaging specialists who have provided a series of expertly written chapters. Each contains a series of carefully chosen images showing the full potential of modern cardiovascular imaging techniques. The ESC Textbook of Cardiovascular Imaging has been designed as a clinically orientated reference, the main aim of which has been to define the role and clinical utility of different cardiovascular imaging modalities in the diagnostic workup of patients following a disease-based approach. Each section presents a structured review of the theory and practice of cardiac imaging, while detailing the application of different modalities in diagnosing cardiovascular disease. The associated website provides readers with access to the electronic version, enriching the user experience through inclusion of a large number of dynamic videos that demonstrate key aspects of cardiovascular imaging. Both videos and still images can be downloaded for use in the readers’ own presentations, while the website also includes dynamic links to other important resources. This book and its associated website are therefore the ideal companion for all cardiologists, trainees and cardiovascular imagers wishing to advance their knowledge in this area. Technical aspects of imaging - Echocardiography: basic principles - New developments in echocardiography - Nuclear cardiology (pet and spect): basic principles - Hybrid imaging: pet–ct and spect–ct - Cardiac ct: basic principles - Cmr: basic principles - Valvular heart disease - Valvular stenosis - Valvular regurgitation - Heart valve prostheses - Endocarditis - Coronary artery disease - Echocardiography and detection of coronary artery disease - Nuclear cardiology and detection of coronary artery disease - Cardiac ct and detection of coronary artery disease - Cmr and detection of coronary artery disease - Heart failure - Evaluation of systolic and diastolic lv function - Echocardiography to assess viability - Nuclear imaging and multi-detector computed tomography to assess viability - Heart failure: cmr to assess viability - Imaging cardiac innervation - Cardiac resynchronization therapy: selection of candidates - Cardiac resynchronization therapy: optimization and follow-up - Cardiomyopathies - Hypertrophic cardiomyopathy - Infiltrative cardiomyopathy - Dilated cardiomyopathy - Arrhythmogenic right ventricular cardiomyopathy/dysplasia (arvc/d) - Peri-myocardial disease - Pericardial effusion and cardiac tamponade - Constrictive pericarditis and restrictive cardiomyopathy - Myocarditis - Cardiac masses and tumours - Adult congenital heart disease - The role of echocardiography in adult congenital heart disease - The roles of cmr and msct in adult congenital heart disease - Aortic disease: aneurysm and dissection - Role of echocardiography - Role of magnetic resonance imaging in aortic disease - Role of multi-slice computed tomography.